1997
DOI: 10.1183/09031936.97.10112596
|View full text |Cite
|
Sign up to set email alerts
|

One year follow-up study of endocrine and lung function of asthmatic children on inhaled budesonide

Abstract: To weigh the benefits and risks of long-term treatment, 12 children with moderately severe asthma were assessed in a follow-up study on budesonide 200 µg b.i.d.After 1 yr, the nocturnal cortisol production was significantly reduced by 19%, but no greater compared to 2 and 4 weeks of treatment. Growth and growth hormone levels were normal. Lung function tests were significantly better, not only versus baseline values but also versus 2 and 4 weeks of treatment.We conclude that systemic effects of inhaled cortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…day -1 BDP as dry powder as well as MDI, although the levels stayed within the normal range. Sustained, but not cumulative, effects on the HPA axis by inhaled steroids have also been demonstrated in a study by NIKOLAIZIK et al [24] over a 1-yr period. These results have to be balanced against the conclusions of other studies which did not find significant variation in either urine or plasma cortisol levels at various doses of BDP [25,26].…”
Section: Discussionmentioning
confidence: 60%
“…day -1 BDP as dry powder as well as MDI, although the levels stayed within the normal range. Sustained, but not cumulative, effects on the HPA axis by inhaled steroids have also been demonstrated in a study by NIKOLAIZIK et al [24] over a 1-yr period. These results have to be balanced against the conclusions of other studies which did not find significant variation in either urine or plasma cortisol levels at various doses of BDP [25,26].…”
Section: Discussionmentioning
confidence: 60%
“…W yatt et al [22] in 1978 and C hang and T am [23] in 1991 have also shown significant changes in urinary cortisol excretion in children on 400 µg·day ‐1 BDP as dry powder as well as MDI, although the levels stayed within the normal range. Sustained, but not cumulative, effects on the HPA axis by inhaled steroids have also been demonstrated in a study by N ikolaizik et al [24] over a 1‐yr period. These results have to be balanced against the conclusions of other studies which did not find significant variation in either urine or plasma cortisol levels at various doses of BDP [25, 26].…”
Section: Discussionmentioning
confidence: 66%
“…With regards to the frequency of testing adrenal function the study reported by Nikolaizik et al is reassuring in that although nocturnal cortisol production was significantly reduced by 19% after one year of treatment, this was no greater than that observed after two and four weeks' treatment. 25 However, their patients were taking low to moderate doses of inhaled glucocorticoids (400 mg/day), and they did not look at adrenal reserve and therefore the capacity to respond to stress. An alternative approach would be to assume that all children on high dose inhaled glucocorticoid have adrenal suppression, and to issue them with steroid cards and recommend glucocorticoid supplementation during stressful illness.…”
Section: Discussionmentioning
confidence: 99%